Effects of data storage on efficiency of financial institutions in Uganda- a case study of Pride Microfinance Limited, Kabalagala branch in Kampala. - Wandera , Sharon Gloria; Modi, Derick (SJ Insights, 2025)
Background: This study aimed at determining the effects of data storage on the efficiency of financial institutions in Uganda- a case study of Pride Microfinance Limited, Kabalagala branch in Kampala. Methodology: A cross-sectional study design for quantitative and qualitative analysis was used on 46 respondents who returned the questionnaires. Data was collected by use of self-administered questionnaires and interview guides. Quantitative data was analyzed at the univariate level based on the mean and frequencies, percentages, and bivariate level using the correlation coefficient with the help of Statistical Package for Social Sciences 7.0 (SPSS). Qualitative data were analyzed by content analysis, by composing explanations and substantiating them using the respondents' open responses. Results: Findings show that the accounting information system provides information on financial performance measuring ratios, providing useful information about the performance of debt in the capital structure that the general manager must try to influence to prove and manage the overall organizational performance. The researcher further found out that AIS provides information about assets in an organization, which helps to do investment planning within Pride Microfinance Limited. The study also recognized that accounting information system enables users to make informed judgments. Since every decision involves several alternatives. It assists the user in deciding their course of action. Accounting is a process that, with the help of accounting records, produces financial statements. It also helps management in their important duties of planning, organizing, leading, supervising, controlling, ‹Intl decision-making. Conclusion: The researcher concluded that AIS affects the overall financial performance of Pride Microfinance Limited at Kabalagala, where it highly influences decisions made, the nature of communication, and efficiency in performance at the financial institution. Recommendation: Therefore, the researcher recommended that Pride Microfinance undertake more awareness programs to create a positive stance towards AIS amongst stakeholders.